Political Reform in Saudi Arabia: Implications of Vision 2030 on International Relations in The Middle East - Muhammad Zaki Mubarak; Mohammad Izdiyan Muttaqin (Publik : (Jurnal Ilmu Administrasi), 2022)
This article discusses the political changes taking place in Saudi Arabia as part of the Vision 2030 reform program and their impact on international relations in the Middle East. Vision 2030 is an ambitious national transformation plan aimed at economic diversification, social modernization, and institutional renewal in Saudi Arabia. In this context, this article investigates the policy implications and steps taken by Saudi Arabia in strengthening their international relations. This research uses a qualitative analysis approach by collecting and analyzing data from various sources related to political changes in Saudi Arabia and their impact on international relations. Research findings show that political reforms undertaken by Saudi Arabia have affected the dynamics of their relations with countries in the Middle East. Vision 2030 provides a broader framework for forging closer economic and political partnerships with neighboring countries, as well as strengthening Saudi Arabia's position in regional and international affairs.